Op soek na'n Mediabestel vir Suid·Afrika - Arnold de Beer (Communicare)
COMMUNICARE encourages the scientific debate. Our last contribu tion is published in response to the article of Tomaselli & Louw In 9(1), who questioned some of the predie tions regarding post-apartheid media In an earlier article by the author pub lished In 8(1). These are his repiles... Prof Keyan Tomaselli, Director of the Cultural Studies Unit at the University of Natal (Durban), is without doubt one of most prolific writers in the field of South African media and communication studies. This is not a matter of c tention; what is at stake in this review article Is the way in which Tomaselll deals with statements and facts in his pub lications. It is argued that Tomaselli Is prone to state a debatable point as a "scientific fact" and then proceeds to build a whole theoretical argument on this and similar "facts". It is fur ther argued that his article: 'Vrye Weekblad' and post-apartheld mania; what to do with the press? is a case In point.